Dichters op reis Moderne Nederlandstalige poëzie over het buitenland - Kalla , Barbara Irena (Lage Landen Studies, 2018)
How do contemporary Dutch-language poets view their neighbouring countries, South and Central Europe and Indonesia? This collection of research articles explores modern travel poetry, a genre which to this day has hardly been paid any attention. Dichters op reis ('Poets travelling') deals with the poetic travelogues of Dutch-language poets, including postcards and a thorough examination of the other, constantly focussing on a confrontation with the poet's own identity, their own past and their being a poet. The reader gains access to different countries and to a wide variety of poetic practices at the same time. And above all else, they get to know wonderful, little-known poems.